Binary Adsorption Studies of Toxic Metal Ions of Lead and Copper from Aqueous Solution by Modified Foeniculum vulgaris Seeds (Fennel Seeds) - Mabungela, Ntandokazi; David Shooto, Ntaote; Mtunzi, Fanyana; Bobby Naidoo, Eliazer (Asian Journal of Chemistry, 2021)
Discharge of copper(II) and lead(II) ions into rivers and streams by industries and other human activities has gained serious consideration from regulatory bodies. These toxic metals are harmful to human beings and aquatic life when in high concentrations. Therefore, their removal from wastewater is very important. Hence, this work reports the binary adsorption of toxic metal ions of Cu(II) and Pb(II) from aqueous solution by pristine and modified fennel seeds. Pristine fennel seeds (PFS) were treated with acidic and alkaline solutions to develop modified adsorbents designated ATFS and BTFS, respectively. SEM images revealed that PFS had an amorphous surface with irregular cavities. However, upon acid and base treatment, the surface was more refined. The ATFS had interconnected pores while BTFS had somewhat honeycomb pores. The UV-Vis results confirmed that some of the components were removed from PFS during acid and base pre-treatment. FTIR spectra revealed that the adsorbents had functional groups such as (-OH) and (-C=O), which were involved in the uptake of the metal ions. It was observed that the uptake of Cu(II) and Pb(II) ions onto all adsorbents progressively increased when the initial concentration of the solution was increased. The maximum adsorption capacity was obtained when the initial concentration of the solution was 100 mg/L. The uptake of Cu(II) and Pb(II) on PFS was 3.345 and 11.524 mg/g. While for ATFS 3.78 and 13.07 mg/g and BTFS 8.143 and 14.85 mg/g, respectively. It was observed that the isotherm data fitted Freundlich better for the uptake of both metal ions onto all adsorbents. It was observed that there was a rapid uptake when contact time increased from 5 to 60 min. However, when time increased above 60 min the uptake stabilized and reached equilibrium this was due to the saturation of active sites on the surface for all adsorbents. The kinetics study revealed that PSO fitted the data better than PFO. IPD data revealed that the uptake of metal ions was controlled by the synergistic of ESA and EPA. The ΔHº values for Cu(II) and Pb(II) uptake onto all adsorbents were all negative. This suggested that the reactions were exothermic.